オーストラリア ナンキョク カンソク タイ ニ サンカ シテ ノ コチジキ ガク ヨウ ガンセキ シリョウ サイシュウ ホウコク 1987 - 船木, 實; フナキ, ミノル; Funaki, Minoru (1988)
P(論文) オーストラリア南極観測隊(ANARE)の1986-87年第6次航海に参加し, 古地磁気学用岩石試料を採集した。採集した試料は501個で, これらはハード島, ラルセマンヒルズ, ヴェストフォールドヒルズ, スカリンモノリスそれにモーソン基地周辺から採集されたものである。ほとんどの試料はエンジンドリルで採集したが, 一部の岩石はハンマーにより採集した。可能な限り試料には太陽コンパスと磁気コンパスの両方で方位を記載した。ANAREは小型ヘリコプターとアップルハット(簡易観測小屋)を野外調査に用い, 効率良い調査を行っていた。 The author participated in voyage 6 of the Australian National Antarctic Research Expedition (ANARE) in the 1986/1987 season in order to collect rock samples for the study of paleomagnetism. A total of 501 samples were obtained from Heard Island, Larsemann Hills, Vestfold Hills, Scullin Monolith and Davis Station areas. The samples were collected mainly with an engine core drill and partially with a hammer. The directions of the samples were determined by the sun and the magnetic compasses. The author was impressed by the efficient field operations of ANARE using small helicopters and portable field huts called Apple Hut. departmental bulletin paper